Integrating academic type of social media activity with perceived academic performance: A role of task-related and non-task-related compulsive Internet use. (October 2019) - Chang, Ching-Ter; Tu, Chang-Shu; Hajiyev, Jeyhun
Abstract: The use of social media and compulsive Internet use among university students has become debatable concern due to both positive and negative effects on academic performance. Yet, little is known about how students' task-on and task-off Internet, as well as social media use, may influence their perceived academic performance. This study differentiates task-related and non-task-related compulsive Internet use and utilizes academic type of social media activity that predicts perceived academic performance with inclusion of task value as external variable and academic motivation as moderator. The SEM analysis of data collected from 489 Turkish students shows that academic type of social media activity and task-related compulsive Internet use positively impact perceived academic performance, while non-task-related compulsive Internet use negatively influences perceived academic performance. Perceived academic performance positively predicts task-related compulsive Internet use of students with a moderation effect of academic motivation. Another interesting finding is that perceived task value positively influences perceived academic performance in the context of non-task-related compulsive Internet use but not task-related compulsive Internet use, which is explained to the extent that the type of Internet use defines whether students value the process of learning (e.g., online searching of study materials, resources, academic contents) or the outcome (e.g., academic grades) mostly. Findings can help educators to lead the students to appropriately use Internet and social media for academic purpose. Because, academic motivation can significantly contribute to students' use of Internet for academic purpose regardless of their need for relief, comfort in case of bad academic performance and grades. Highlights: Academic type of social media use strongly impacts perceived academic performance. Perceived academic performance has strong impact on task-related CIU. Perceived academic performance does not have strong impact on non-task-related CIU. Academic motivation is a strong moderator in terms of task-related CIU. Task value affects perceived academic performance in terms of non-task-related CIU.